THE INTRODUCTION OF HIJAIYAH LETTERS USING AN INTENSIVE PARTICIPATORY METHOD IN CHILDREN - Dyla Fajhriani N; Nurul Jariah; Ulfah Dwi Januarti; Indah Fajriani; Febriyeni Nasrul (Al-Ashr : Jurnal Pendidikan dan Pembelajaran Dasar, 2026)
This study aims to describe the process and effectiveness of introducing the hijaiyah letters using the intensive participatory method for children aged 7–10 years. The intensive participatory method emphasizes active student involvement through reading, writing, educational games, and two-way interaction between teachers and students. This study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation at the AHE reading tutoring institution. The results showed that the intensive participatory method was able to improve children's understanding of the shape, sound, and pronunciation of the hijaiyah letters more effectively than conventional learning. Children appeared more enthusiastic, actively asked questions, and were able to recognize letters with a higher level of accuracy. Furthermore, direct involvement in participatory activities strengthened children's memory and increased their confidence in reading the hijaiyah letters. This study concludes that the intensive participatory method can be an effective alternative learning strategy for introducing the hijaiyah letters to elementary school-aged children.